THE CORRELATION BETWEEN STUDENTS’ READING MOTIVATION AND THEIR READING COMPREHENSION - Dewi, Larasati Muthia; Safitri, Yuni (PROJECT (Professional Journal of English Education), 2018)
This research objects to analyze the relation of students’ reading motivation and reading comprehension among junior high school students in Cimahi, West Java Province, Indonesia. Participants of this research were 33 students of eight grade at SMPN 5 Cimahi, the research was conducted with a quantitative approach and performed in Cimahi, Bandung. Based on the result show that, there is no significant correlation in Students’ Reading motivation because the data show the significant is 0,736 more than 0,05 (> 0,05). The result also show that there is no significant correlation in Reading comprehension because in the data show the significant is 0,376 more than 0,05 ( > 0,05). Beside on the data obtained from 33 students showed that high motivation of reading is 3,3%, medium motivation of reading is 96,7% and not low motivation of reading.  Measurement of students reading motivation was done by using MRQ by Wigfeld, John and Guthrie (1996) and reading comprehension test used narrative text. However, the researchers give a suggestion for teacher to be able to create fun and interesting activity. Such as give interesting text book in reading comprehension, it will help the students to have high reading motivation to read more English text and understand the context.